Cathelicidin anti-microbial peptides : characterization of cathelicidin gene family members in Rock ptarmigan - Hallgrímur Steinsson 1978- (2017)
Cathelicidins are a class of antimicrobial peptides expressed in vertebrate species which are part of the innate immune system. The aim of this thesis was to resolve genomic organization of the cathelicidin gene cluster in rock ptarmigan (Lagopus muta) and to predict the amino sequence of the mature peptides and analyze expression. To locate the cathelicidin genes the chicken (Gallus gallus) genome sequences were used to blast a novel draft genome of rock ptarmigan. The draft genome was subsequently used to design primers for PCR and sequencing, to enable obtaining the entire cathelicidin cluster. The characterization of the cathelicidin cluster in rock ptarmigan revealed all four cathelicidin genes orthologues found in chicken and turkey (Meleagris gallopavo), namely CATHL1, CATH2, CATH3, CATHB1, flanked by KLH18 and TBRG4, in the same order on chromosome 2. The genes map to a 15kb region, which is of similar size in chicken. The quality of the region is good except for two minor gaps of ~100bp. The sequence harbored the exons coding for the mature peptide for all four cathelicidin genes. Analysis by RT-qPCR revealed that all cathelicidins were expressed, using RNA isolated from eight tissues. Translation of the open reading frames of the cathelicidins revealed substitution in all four genes in rock ptarmigan. CATHL1, CATH2, CATH3 showing greatest similarity to chicken but CATHB1 to turkey. Cathelicidin eru örverudrepandi peptíð í hryggdýrum sem eru hluti af meðfædda ónæmiskerfi hryggdýra. Markmið verkefnisins var að skilgreina cathelicidin genasvæðið í fjallrjúpu og að spá fyrir um aminosýruröð peptíðanna og tjáningu þeirra. Fjögur cathelicidin prótín eru tjáð í kjúkling (Gallus gallus) og voru þær raðir notaðar til að staðsetja genin í fjallrjúpu (Lagopus muta) með notkun nýlega samsetts erfðamengis. Erfðamengið var síðan notað til að hanna PCR primera til að geta raðgreint cathelicidin svæðið að fullu. Skilgreiningin á cathelicidin svæðinu leiddi í ljós að öll cathelicidin genin sem kjúklingar og kalkúnar ...